Interrelations of Behavioral, Emotional, and Cognitive School Engagement in High School Students. - Li, Yibing; Lerner, Richard (Journal of Youth & Adolescence, 2013)
School engagement, or the extent to which students are involved in, attached and committed to the academic and social activities in school, plays a prominent role in preventing academic failure, promoting competence, and influencing a wide range of adolescent outcomes. Although the multidimensional nature of school engagement is well-recognized, how the three purported parts of the construct work together is largely unknown. By using data from the longitudinal, 4-H study of Positive Youth Development, involving a sample of 1,029 adolescents (67.7 % female; mean age at Grade 9 = 14.92 years; 74.4 % of participants were European American, 5.2 % were Latino/a, 7.3 % were African American), the current study examined the interrelationships of behavioral, emotional, and cognitive aspects of school engagement over three years in adolescence (Grades 9-11). We used autoregressive lagged effects models to assess the relationships among the three engagement constructs. Results indicated that behavioral and emotional engagement were related bidirectionally (each variable was a basis and an outcome of the other). In addition, behavioral engagement influenced cognitive engagement (but the reverse of this relation was not found). Implications for future research are discussed.